DILEMA PENDIDIKAN DAN MISI GEREJA - Yehezkiel Sugeng Mulyono (Metanoia, 2020)
Churches in Indonesia must think carefully how to take part in advancing education in Indonesia. Education and the church must prepare for a golden generation of Indonesia. Children who are studying in early childhood education institutions and elementary schools, will be the stylist and leader of the unitary state of the Republic of Indonesia. The role of the church in education must be real. That proportion must be clear. Why? Because the church is not likely to get recognition in education if he is not able to provide benefits. This is a problem that the church must take seriously. The main solution to the main problems of education is the procurement of human resources that are oriented to excellence, professional expertise, visionary, and highly competitive. Human resources like this will have high confidence and skills according to market bargaining power. In addition, the provision of useful and quality facilities in accordance with the demands of the needs, by donating human resources and facilities like that, obviously the church has supported the government to realize the goals of National Education